Comparison of efficiency of in vitro cloned sheep embryo production by conventional somatic cell nuclear transfer and handmade cloning technique. (22nd January 2018) - Khan, S; Tali, M; Khan, A; Bhat, S; Ashraf, A; Bhat, MH; Khan, F; Shah, RA
Contents: Conventional somatic cell nuclear transfer (SCNT) technique of in vitro production of cloned embryos involves use of costly and complicated micromanipulators. Handmade cloning (HMC) technique has been applied as efficient and cost‐effective alternative in many livestock species. The aim of the present study was to compare the efficiency of in vitro production and in vitro development of cloned sheep embryos by the two techniques. Cloned embryos were produced by conventional SCNT using micromanipulator apparatus and by HMC technique. Enucleation efficiency and efficiency of fusion with somatic cell (nucleus donor) were compared. Cleavage percentage was observed on day 2 of in vitro culture (IVC), and morula and blastocyst percentages were calculated on day 7 of IVC. Higher enucleation efficiency (96.98 ± 1.01 vs. 93.62 ± 1.03; p  > .05) as well as fusion efficiency was obtained with HMC technique than with conventional SCNT (96.26 ± 1.34 vs. 92.63 ± 0.70, p  < .05); 181 cloned sheep embryos were produced in vitro by conventional SCNT and 92 by HMC. Cleavage percentage observed on day 2 of in vitro culture was higher in HMC than SCNT (66.92 ± 3.72 vs. 55.97 ± 2.5, respectively, p  < .05). Morula percentage obtained was higher in SCNT than HMC (44.12 ± 2.93 vs. 30.43 ± 6.79, respectively, p  < .05), whereas blastocyst percentage obtained by HMC was higher (12.46 ± 4.96) than SCNT (5.31 ± 2.25; p  > .05). It was inferred that HMC technique provides a cost‐effective and efficient method of in vitro production of cloned sheep embryos with a comparatively simpler technique with a possibility of automation. Efficiency of cloned embryo production could be improved further by propagating and standardizing this technique.